THE ANALYSIS OF CLAUSE COMPLEX OF ANALYTICAL EXPOSITION TEXTS WRITTEN BY THE ENGLISH TEACHERS OF SMKN 2 PALANGKA RAYA - Charly Kurniawan; Maria Arina Luardini; Elanneri Karani (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2021)
This study was conducted to investigate the analysis of clause complex of analytical exposition text written by the English teachers of SMKN 2 Palangka Raya. Considering that teachers have important role in education field, in which teachers have a function as the model in teaching learning process, especially in teaching English and it is the consideration that the subjects of the study will be the English teachers. The study design of this study was descriptive qualitative. By means of a descriptive study under Systemic Functional Linguistics theory as suggested by Halliday & Matthiessen (2014), the writers employ the analysis of taxis systems which cover elaboration, extension, and enhancement. Besides, logico-semantic relation is also analyzed which covers projection and expansion The data will be analyzed through systemic functional approach in which the analysis of the data will be based the clauses and its taxis (protasis and hypotaxis) along with its logico-semantic relations from text by the teacher.